Propanol Vapor Sensor Utilizing Air-Gap as Sensing Part of the Mach-Zehnder Interferometer - Issa, Dhuha N.; Taher, Hanan J.; Mohammed, Saif A. (Iraqi Journal of Laser, 2019)
The purpose of this study is to demonstrate a simple high sensitivity vapor sensor for propanol ((CH3)2CHOH). A free space gap was employed in two arms of a Mach-Zehnder interferometer to serve as the sensing mechanism by adding propanol volume (0.2, 0.4, 0.6, 0.8, and 1) ml and to set the phase reference with a physical spacing of (0.5, 1, 1.5, and 2) mm. The propagation constant of transmitted light in the Mach-Zehnder interferometer’s gap changes due to the small variation in the refractive index inside sensing arm that will further shift the optical phase of the signal. Experimental results indicated that the highest sensitivity of propanol was about 0.0275 nm/ml in different liquid volume while highest phase shift was 0.182×103 in liquid volume 0.2 ml for spacing 1 mm.